Noradrenaline producing phaeochromocytomas with absent pressor response to beta-blockade. - Plouin, P F (1979)
In 2 patients with phaeochromocytoma, effective beta-blockade was obtained with propranolol (40 mg twice a day for 3 days) or acebutolol (400 mg twice a day for 3 days) without any effect on the blood pressure. In both patients the excretion of noradrenaline predominated over that of adrenaline, a picture found in most cases of phaeochromocytoma. A hypertensive response to beta-blockade might be expected in patients with an adrenaline-secreting tumour. It cannot be a regular event or constitute a diagnostic test in patients with suspected phaeochromocytoma.